DISKURSUS POLITIK DALAM PROSES PEMEKARAN WILAYAH PANTAI TIMUR (Study Kasus Kab. OKI Kawasan Timur OKI Wilayah Pantai Timur) - Fitri Herdayani (STIA Bengkulu, 2024)
The study aims to analyze about the regional development about discourse of the Pantai Timur region that wants the separation of the autonomy region of the Ogan Komering Ilir district that has a long process of journey from various local political elite. The method of research, using qualitative-descriptive method which is an inquiry strategy more pressing in search of meaning, using the Pareto political elite theory (1984-1923). Data are collected by interview techniques, data collection, data reduction, data presentation and conclusion. The results of this study found that. (1), that the discourse of the Pantai Timur development is the needs of the community, initiated local elites by building communications at government levels and community-level support. (2) the process of establishing a new district has a lot of constraints caused by the change of law from the central government in 2014. Therefore, the aspirations of the political elite and support of the regional community still have a long journey and process in creating new districts to achieve and earn positions and power in the new government institution.